Prevention and Treatment of Age-Related Diseases
DOI: 10.1007/1-4020-5058-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Skin Aging: Pathogenesis, Prevention and Treatment

Abstract: Skin aging is a consequence of genetically programmed processes of intrinsic aging and extrinsic aging caused by ultraviolet light and other environmental insults. There are many different approaches to reduce or postpone the untoward effects of intrinsic programmed aging and extrinsic environmental injury. The prevention of extrinsic aging utilizes various methods of photoprotection and antioxidants. Treatments of aged skin are not limited to a single procedure but may consist of a combination of many adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have elegantly demonstrated that UV radiation can simultaneously reduce collagen synthesis and increase collagen degradation thereby resulting in a reduction of skin collagen with age in an accelerated manner [1,2,[15][16][17][18][19]. However, this concept seems inconsistent with a widely cited pioneering study in 1975 demonstrating that total collagen contents from skin exposed or not exposed to sunlight in Caucasian whites over a wide range of age were practically the same [20].…”
Section: New Alternative Skin Aging/anti-aging Theorymentioning
confidence: 99%
“…Numerous studies have elegantly demonstrated that UV radiation can simultaneously reduce collagen synthesis and increase collagen degradation thereby resulting in a reduction of skin collagen with age in an accelerated manner [1,2,[15][16][17][18][19]. However, this concept seems inconsistent with a widely cited pioneering study in 1975 demonstrating that total collagen contents from skin exposed or not exposed to sunlight in Caucasian whites over a wide range of age were practically the same [20].…”
Section: New Alternative Skin Aging/anti-aging Theorymentioning
confidence: 99%